Pelaksanaan Precautionary Principle Dalam Menterjemahkan Pembangunan Berkelanjutan Analisis Kritis Putusan Kasus Kasus Perdata Mandalawangi Garut dan Kalista Alam Meulaboh Aceh - Anastasia Pratiwi, Bella (LPPM Universitas Ekasakti Padang, 2024)
Sustainable Development is one of the environmental principles to achieve which cannot be separated from the implementation of other environmental principles. One of the most important principles to be implemented so that the goal of sustainable development, where future generations can enjoy the right to a good environment, is to be careful in using the natural resources we have now. In practice, the precautionary principle is often violated by maladministration in the issuance of permits. If a pollution has occurred, the judge becomes one of the pillars in terms of efforts to obtain compensation to make the maximum possible repairs for the losses created.